2017
DOI: 10.3748/wjg.v23.i29.5405
|View full text |Cite
|
Sign up to set email alerts
|

Transition clinic attendance is associated with improved beliefs and attitudes toward medicine in patients with inflammatory bowel disease

Abstract: AIMTo evaluated the differences in knowledge, adherence, attitudes, and beliefs about medicine in adolescents with inflammatory bowel disease (IBD) attending transition clinics.METHODSWe prospectively enrolled patients from July 2012 to June 2013. All adolescents who attended a tertiary-centre-based dedicated IBD transition clinic were invited to participate. Adolescent controls were recruited from university-affiliated gastroenterology offices. Participants completed questionnaires about their disease and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In a prospective study conducted in Canada, pediatric patients attending a transition clinic had stronger beliefs regarding the necessity for IBD drugs ( P =0.004), were less skeptical (7% vs. 21%, P =0.03), and were more ambivalent (61% vs. 34%, P =0.004) in terms of their attitudes toward medicine than a control group, although self-reported adherence was not statistically different compared with controls [92]. In a retrospective study conducted in the United Kingdom, patients who experienced a transition program showed a higher percentage of medication adherence (89% vs. 46%, P =0.002), a lower surgical rate (25% vs. 46%, P =0.01) or hospitalization rate (29% vs. 61%, P =0.002) within 2 years of transfer, and a lower rate of nonattendance at the clinic (29% vs. 78%, P =0.001) than those who did not [93].…”
Section: Outcomes Of Transitionmentioning
confidence: 99%
“…In a prospective study conducted in Canada, pediatric patients attending a transition clinic had stronger beliefs regarding the necessity for IBD drugs ( P =0.004), were less skeptical (7% vs. 21%, P =0.03), and were more ambivalent (61% vs. 34%, P =0.004) in terms of their attitudes toward medicine than a control group, although self-reported adherence was not statistically different compared with controls [92]. In a retrospective study conducted in the United Kingdom, patients who experienced a transition program showed a higher percentage of medication adherence (89% vs. 46%, P =0.002), a lower surgical rate (25% vs. 46%, P =0.01) or hospitalization rate (29% vs. 61%, P =0.002) within 2 years of transfer, and a lower rate of nonattendance at the clinic (29% vs. 78%, P =0.001) than those who did not [93].…”
Section: Outcomes Of Transitionmentioning
confidence: 99%
“…7 Joint visits were the most frequently applied interventions, which were held under different circumstances and were organised by multidisciplinary groups of different compositions all around the world. [8][9][10][11][12] Non-randomised studies with low sample sizes and selection bias showed that joint visits may improve quality of life, medical adherence, patients' satisfaction and able to optimise medical visit attendance rates. 8 13-17 However, patient education programmes and the coordinating role of IBD nurses are also considered to be beneficial in structured transition interventions.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, given the small sample sizes and retrospective methods of many of these studies, more research is needed to affirm their effectiveness. In addition, literature on integrating transitional strategies into standard care, particularly in IBD, appears to also be promising, but-to date-these studies have not included objective outcomes such as adherence [46,47].…”
Section: Transfer Clinic Programsmentioning
confidence: 99%